Isolated Diastolic Hypertension and Risk of Cardiovascular Events: A Systematic Review and Meta-Analysis of Cohort Studies With 489,814 Participants - Huang, Mingyan; Long, Linzi; Tan, Ling; Shen, Aling; Deng, Mi; Peng, Yuxuan; Yang, Wenwen; Li, Hongzheng; Wei, Yue; Li, Meng; Liao, Feifei; Liu, Chao; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The association between isolated diastolic hypertension (IDH) and cardiovascular events has been inconsistently reported. This meta-analysis of cohort studies was designed to investigate the effect of the 2018 European Society of Cardiology (ESC) definition of IDH on the risk of composite cardiovascular events, cardiovascular mortality, all-cause mortality, and all strokes including ischemic stroke (IS) and hemorrhagic stroke (HS). Methods: PubMed, Embase, the Cochrane Library, and Web of Science were searched from inception to July 6, 2021. Cohort studies that investigated the association between IDH and cardiovascular events risk, compared to normotension, were included. Pooled hazard ratios (HRs) and 95% CIs were calculated using a random-effects models and heterogeneity was evaluated using Q-test and I2 statistic. The robustness of the associations was identified using sensitivity analysis. The methodological quality of the studies was assessed using the Newcastle–Ottawa scale. Publication bias was assessed using funnel plot, trim-and-fill method, Begg's test, and Egger's test. Results: A total of 15 cohort studies (13 articles) including 489,814 participants were included in this meta-analysis. The follow-up period ranged from 4.3 to 29 years. IDH was significantly associated with an increased risk of composite cardiovascular events (HR 1.28, 95% CI: 1.07–1.52, p = 0.006), cardiovascular mortality (HR 1.45, 95% CI: 1.07–1.95, p = 0.015), all strokes (HR 1.44, 95% CI: 1.04–2.01, p = 0.03), and HS (HR 1.64, 95% CI: 1.18–2.29, p = 0.164), but not associated with all-cause mortality (HR 1.20, 95% CI: 0.97–1.47, p = 0.087) and IS (HR 1.56, 95% CI: 0.87–2.81, p = 0.137). Subgroup analysis further indicated that IDH in the younger patients (mean age ≤ 55 years) and from Asia were significantly associated with an increased risk of composite cardiovascular events, while the elderly patients (mean age ≥ 55 years), Americans, and Europeans were not significantly associated with an increased risk of composite cardiovascular events. Conclusion: This meta-analysis provides evidence that IDH defined using the 2018 ESC criterion is significantly associated with an increased risk of composite cardiovascular events, cardiovascular mortality, all strokes and HS, but not significantly associated with all-cause death and IS. These findings also emphasize the importance for patients with IDH to have their blood pressure within normal, especially in the young adults and Asians. Trial Registration: PROSPERO, Identifier: CRD42021254108.